Stray dogs of northern Jordan as reservoirs of ticks and tick-borne hemopathogens - Qablan, Moneeb Ahmad; Kubelová, Michaela; Siroký, Pavel; Modrý, David; Amr, Zuhair Sami (Parasitology research, 2012)
Dogs are competent reservoir hosts of several hemopathogens including zoonotic agents and can serve as readily available source of nutrition for many blood-feeding arthropods. Three hemopathogens had been detected for the first time in Jordan. The PCR prevalence of Anaplasma phagocytophilum, Hepatozoon canis, and piroplasmid DNA were 39.5%, 28.9%, and 7.9% (n=38) respectively. Sequencing of amplicons of PCR with universal primers targeting the 18S rRNA gene of piroplasmids shows the highest similarity to equine piroplasmids species Theileria equi from two dogs and Babesia caballi from a single dog. Ticks of two genera Rhipicephalus and Haemaphysalis, were detected in this study (n=268). The brown dog tick, Rhipicephalus sanguineus was the most abundant species (95.1%, n=255), followed by Haemaphysalis erinacei (3%, n=8) and Haemaphysalis parva (1.9%, n=5). The two Haemaphysalis species were detected for the first time from dogs in Jordan. Regarding its high prevalence, we expect R. sanguineus being a possible vector of detected pathogens.
Keywords: Molecular Sequence Data; Blood; Sequence Analysis, DNA; zdroje nemoci; psi; Jordan; Babesia; polymerázová řetězová reakce; Polymerase Chain Reaction; Dogs; mužské pohlaví; Dog Diseases; Ectoparasitic Infestations; krev; nemoci psů; ženské pohlaví; zvířata; Anaplasma phagocytophilum; Jordánsko; Ixodidae; infestace ektoparazity; sekvenční analýza DNA; nemoci přenášené klíšťaty; Coccidia; Tick-Borne Diseases; molekulární sekvence - údaje; Disease Reservoirs; Female; Theileria; Male; Animals